2017
DOI: 10.3389/fpsyt.2017.00092
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Trauma-Focused Cognitive-Behavioural Therapy for Post-traumatic Stress and Psychotic Symptoms: A Case-Series Study Using Imaginal Reprocessing Strategies

Abstract: Despite high rates of trauma in individuals with psychotic symptoms, post-traumatic stress symptoms are frequently overlooked in clinical practice. There is also reluctance to treat post-traumatic symptoms in case the therapeutic procedure of reprocessing the trauma exacerbates psychotic symptoms. Recent evidence demonstrates that it is safe to use reprocessing strategies in this population. However, most published studies have been based on treating post-traumatic symptoms in isolation from psychotic symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 80 publications
(102 reference statements)
2
33
0
2
Order By: Relevance
“…Although the precision of this finding is small (given the small sample size), it may be attributable to the type of trauma therapy administered. Keen et al (2017) reported a high drop-out rate (35.6%) in their case-series (n = 14) of prolonged exposure in veterans with PTSD and psychosis. Their qualitative analysis showed that drop-out was mostly related to fear about their ability to manage distress associated with the reliving of the hot part of traumatic memories during PE.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although the precision of this finding is small (given the small sample size), it may be attributable to the type of trauma therapy administered. Keen et al (2017) reported a high drop-out rate (35.6%) in their case-series (n = 14) of prolonged exposure in veterans with PTSD and psychosis. Their qualitative analysis showed that drop-out was mostly related to fear about their ability to manage distress associated with the reliving of the hot part of traumatic memories during PE.…”
Section: Discussionmentioning
confidence: 95%
“…First, exposure-based interventions may not be tolerated at a level sufficient to produce effects on voice hearing experiences. Of note, Keen et al (2017) link the high drop-out rates seen when using prolonged exposure with psychosis to fear and avoidance of the reliving of traumatic memories. Second, exposure-based interventions may not work on the mechanisms which underlie the link between trauma symptoms and hearing voices [see Hardy (2017) for a discussion of a number of possible underlying mechanisms].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of the impact of trauma interventions on psychosis found small effects on positive symptoms that were not maintained at follow-up, and small effects on trauma symptoms that were only significant at follow-up (Brand et al, 2018). A case series of imagery rehearsal for nightmares in people with psychosis also found reductions in nightmare-related distress but not psychosis (Sheaves et al, 2015), and a clinical case series of imaginal reprocessing based on individualized formulation of people's trauma and psychosis showed promising results, although more conclusively in measures of trauma than psychosis (Keen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…17 . In some cases, dissociative symptoms may be very disruptive and prevent access to the other targets; in this case they can be prioritized and targeted using sensory grounding techniques to help the individual reliably regain contact with present external stimuli 97,98 .…”
Section: Discussionmentioning
confidence: 99%